2021
DOI: 10.3389/fsufs.2021.643225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Apple Root-Associated Endophytic Streptomyces pulveraceus Strain ES16 by an OSMAC-Assisted Metabolomics Approach

Abstract: The One Strain Many Compounds approach (OSMAC) is a powerful and comprehensive method that enables the chemo-diversity evaluation of microorganisms. This is achieved by variations of physicochemical cultivation parameters and by providing biotic and abiotic triggers to mimic microorganisms' natural environment in the lab. This approach can reactivate the silent biosynthetic routes of specific metabolites typically not biosynthesized under standard laboratory conditions. In the present study, we combined the OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The above results indicated that strain QSB-6 is a good biological control agent against Fusarium . However, Many biocontrol bacterial strains are sensitive to external conditions (i.e., light, high temperature, soil pH extremes), resulting in poor control efficacy in the field ( Alabouvette et al, 2009 ; Armin et al, 2021 ). We therefore investigated the physical and chemical properties of extracellular metabolites from strain QSB-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results indicated that strain QSB-6 is a good biological control agent against Fusarium . However, Many biocontrol bacterial strains are sensitive to external conditions (i.e., light, high temperature, soil pH extremes), resulting in poor control efficacy in the field ( Alabouvette et al, 2009 ; Armin et al, 2021 ). We therefore investigated the physical and chemical properties of extracellular metabolites from strain QSB-6.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial substances produced by specific strains also differ. Antibacterial substances that inhibit pathogens tend not to act alone, but instead two or more antibacterial substances act synergistically to produce antibacterial effects ( Hyakumachi et al, 2014 ; Carrión et al, 2019 ; Joo et al, 2020 ; Newman and Cragg, 2020 ; Armin et al, 2021 ). 2,4-Diacetylphloroglucinol (DAPG) and phenazines (PHZ) produced by Pseudomonas species have been used as antibiotics to control disease suppressive soils and Fusarium wilt ( Weller et al, 2002 ; Haas and Defago, 2005 ; Mazurier et al, 2009 ; Raaijmakers and Mazzola, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the One Strain Many Compounds (OSMAC) approach enables the researchers to explore the chemodiversity of microorganisms ( Figure 2 ). In one such study involving an OSMAC-assisted metabolomics approach, Armin et al (2021a) investigated the metabolic potential of Streptomyces pulveraceus strain ES16 (an apple-associated root endophytic bacteria) by growing it in six different media (ranging from nutrient-rich to minimal media) for a period of 3, 7, and 14 days. Using various state-of-art techniques such as SPME-GC-MS (for expressed volatilome), HPLC-HRMS n (to target the expressed metabolome), and MALDI-HRMSI (for spatial-temporal visualization of metabolites), the authors demonstrated the production of geosmin (a volatile chemical that attracts soil arthropods), mirubactin (iron-chelating siderophore) and polycyclic tetramate macrolactams (biocontrol activity against various pathogens) under stress conditions ( Armin et al, 2021a ).…”
Section: Metabolomics For Investigation Of Endophyte Metabolomementioning
confidence: 99%
“…In one such study involving an OSMAC-assisted metabolomics approach, Armin et al (2021a) investigated the metabolic potential of Streptomyces pulveraceus strain ES16 (an apple-associated root endophytic bacteria) by growing it in six different media (ranging from nutrient-rich to minimal media) for a period of 3, 7, and 14 days. Using various state-of-art techniques such as SPME-GC-MS (for expressed volatilome), HPLC-HRMS n (to target the expressed metabolome), and MALDI-HRMSI (for spatial-temporal visualization of metabolites), the authors demonstrated the production of geosmin (a volatile chemical that attracts soil arthropods), mirubactin (iron-chelating siderophore) and polycyclic tetramate macrolactams (biocontrol activity against various pathogens) under stress conditions ( Armin et al, 2021a ). In addition to chemical OSMAC (by alteration/optimization of chemical media), biological OSMAC involving interaction with other microbial species (endophytic or pathogenic) can be used to increase the diversity of endophyte-derived bioactive compounds ( Armin et al, 2021b ).…”
Section: Metabolomics For Investigation Of Endophyte Metabolomementioning
confidence: 99%
“…These included modified 523 medium, Glucose Yeast Malt medium (GYM), Lysogeny medium (LB), nutrient medium (agar, NA; broth, NB), potato dextrose medium (agar, PDA; broth, PDB), and streptomyces medium (SM). The OSMAC conditions, physio-chemical triggers, and selection pressures presented by each of these six media were recently published [68]. The components of the media are detailed in Table S1.…”
Section: Osmac-assisted Cultivation and Fermentationmentioning
confidence: 99%